2019
DOI: 10.1002/asia.201900732
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Screening and Design of Metal–Organic Frameworks for CH4/N2 Separation

Abstract: CH 4 /N 2 separation is one of the great challenges in gas separation, which is of scientifica nd practical importance, such as in the upgrading of unconventional natural gas. Unfortunately,t he separation performance is still quite low so far mainly due to their very close physical properties. In this work, ah igh-throughput computational screening method was performed to developm etal-organic frameworks (MOFs)f or efficient CH 4 /N 2 separation. General designing rules as wella st he correlation betweens ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Compared with zeolites, MOFs are a relatively new family of nanoporous materials, which are constructed by self‐assembly between inorganic centers (metals or metal oxides) and organic building blocks 15 . Due to the ultrahigh surface areas and high porosity, MOFs give much higher gas uptake capacities compared to other adsorbents and are considered as versatile materials for gas storage, 16 gas separation, 17 senor, 18 molecular catalysis, 19 drug delivery, 20 and so on. MOFs offer a large parameter space to rationally design the size, shape, and functionality of pores with high adsorption and/or diffusion selectivity toward the molecule of interest 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with zeolites, MOFs are a relatively new family of nanoporous materials, which are constructed by self‐assembly between inorganic centers (metals or metal oxides) and organic building blocks 15 . Due to the ultrahigh surface areas and high porosity, MOFs give much higher gas uptake capacities compared to other adsorbents and are considered as versatile materials for gas storage, 16 gas separation, 17 senor, 18 molecular catalysis, 19 drug delivery, 20 and so on. MOFs offer a large parameter space to rationally design the size, shape, and functionality of pores with high adsorption and/or diffusion selectivity toward the molecule of interest 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the similarity in the physical features of both gases limiting the CH 4 /N 2 mixture selectivity. 24 Nevertheless, APSs of MOFs (0.2–30.7 mol/kg) are slightly higher than those of COFs (0.7–16.2 mol/kg). Still, COFs can be used as alternative adsorbents because they show better stabilities than MOFs under harsh chemical conditions, which may make COFs preferable for practical applications over MOFs.…”
Section: Results and Discussionmentioning
confidence: 90%
“… 18 22 A total of 4350 MOFs were studied for CH 4 /H 2 mixture separation at VSA and PSA conditions, and CH 4 /H 2 selectivities of MOFs were predicted based on the porosity and the largest cavity diameter (LCD) of MOFs, and the difference between the heat of adsorption values of gases (Δ Q st ) in MOFs. 23 Yan et al 24 used molecular simulations to examine CH 4 /N 2 mixture separation potentials of 5109 MOFs and revealed that MOFs with pore-limiting diameters (PLDs) in the range of 3.8–4.7 Å achieve high selectivities. Borah and Ponraj screened about 12 000 MOFs for C 2 H 6 /CH 4 separation and highlighted that MOFs with the Zr 4+ cation are promising candidates for purification of CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…, adsorption selectivity vs. working capacity) and their overall performances may still be comparable to the top adsorbents determined in this work. Yan et al 30 performed high-throughput screening of computation-ready, experimental (CoRE) MOFs 58 for the CH 4 /N 2 separation around ambient conditions and determined that some of the MOFs can achieve CH 4 /N 2 selectivities ∼20. While such selectivities seem much higher than those of top MTV-MOFs identified in this work, it should be reminded that they were attained at a lower adsorption pressure than that in this work (1 vs. 10 bar).…”
Section: Resultsmentioning
confidence: 99%
“…The top adsorbent has also been reported as one of the top materials for the membrane-based separation with a CH 4 /N 2 membrane selectivity of 10.26 and CH 4 permeability of 2.61 × 10 6 Barrer. Yan et al 30 performed a high-throughput computational screening of >300 000 MOFs for separation of equimolar CH 4 /N 2 (50/50) separation at ambient conditions and the highest CH 4 /N 2 selectivity was reported as 29.5. Gulbalkan et al 31 recently screened a large collection of MOFs and covalent-organic frameworks (COFs) composed of 5034 materials for CH 4 /N 2 separation at pressure-swing adsorption operation conditions and the highest CH 4 /N 2 selectivity was around 14.…”
Section: Introductionmentioning
confidence: 99%